Phenotypic change and induction of cytokeratin expression during in vitro culture of corneal stromal cells - Sidney, Laura E.; McIntosh, Owen D.; Hopkinson, Andrew (ARVO, 2015)
Purpose: Cells of the corneal epithelium and stroma can be distinguished in vivo by different intermediate filaments, cytokeratins for corneal epithelial cells (CEC) and vimentin for keratocytes. Isolated and cultured keratocytes change phenotype, losing expression of keratocyte markers and gaining markers associated with mesenchymal stromal cells (MSC). This study investigates this change in phenotype in relation to intermediate filament expression in cultured corneal stromal cells (CSC) compared to CEC.